Imagens digitais na análise do uso da terra de uma microbacia como subsídio ao desenvolvimento sustentável - Campos, Sergio [UNESP]; Pissarra, Teresa Cristina Tarlé [UNESP]; Rodrigues, Flávia Mazzer [UNESP]; Silva, Mariana Garcia da [UNESP]; Soares, Muriel Ciccati Emanoele [UNESP]; Granato, Marina [UNESP]; Cavasini, Raquel [UNESP]; Moreira, Katiuscia Fernandes [UNESP] (My University, 2010)
The present work sought to discriminate, to map and to quantify the areas of soil use of the Stream Monte Belo watershed - Botucatu (SP), obtained by digitale images. The cartographic bases were the shart planialtimetric, edited by IBGE (1969) and the satellite images LANDSAT - 7, passages of 21/01/1999, 08/01/2003 and 23/10/2006. The Software Idrisi Andes 15.0 were used for conversion of the analogical information for digital and for determination of the vegetable coverings areas. The results allowed to verify that the SIG - IDRISI Andes 15.0 were efficient in the quantification of the areas with soil use and that the analysis of the data showed a cash progress of the areas of reforestations to the detriment of the areas of pastures, especially from 1999, 2003 to 2006, when the field areas were substituted by the forestry in his totality. In spite of that progress, the forest areas that you correspond to the Permanent Preservation Areas, They are considerably preserved. That result comes to the encounter of the tendency of expansion of the forestry, especially after the installation of cellulose industries in the area, what worsened the environmental problems originating from of the practice of the monoculture.

Este trabalho visou discriminar, mapear e quantificar as áreas de uso da terra da microbacia do Ribeirão Monte Belo - Botucatu (SP), obtido por imagens digitais. As bases cartográficas foram a carta planialtimétrica, editada pelo IBGE (1969) e as imagens de satélite LANDSAT – 5 e 7, passagens de 21/01/1999, 08/01/2003 e 23/10/2006. O software Idrisi Andes 15.0 foi utilizado para conversão da informação analógica para digital e para determinação das áreas das coberturas vegetais. Os resultados permitiram constatar que o Sistema de Informação Geográfica – IDRISI Andes 15.0 foi eficiente na quantificação das áreas com uso da terra e que a análise dos dados mostrou um efetivo avanço das áreas de reflorestamentos em detrimento das áreas de pastagens, especialmente de 1999, 2003 e 2006, quando as áreas de campo foram substituídas pela silvicultura em sua totalidade. Apesar desse avanço, as áreas de mata que correspondem às Áreas de Preservação Permanente estão consideravelmente preservadas. Esse resultado vem ao encontro da tendência de expansão da silvicultura, especialmente após a instalação de indústrias de celulose na região, o que agravou os problemas ambientais oriundos da prática da monocultura.
Digital images in the analysis of the soil use of a watershed as subsidy to the maintainable development
Keywords: Soil use; Geoprocessing; Remote sensing; Uso da terra; Geoprocessamento; Sensoriamento remoto